High prevalence of malnutrition among hospitalized patients at Kabupaten Bekasi general hospital: A critical need for early nutritional screening - Maharani, Ni Ketut Ayu; Kusaeri, Yuliyana (World Nutrition Journal, 2025)
Malnutrition in hospitals is a critical concern that significantly impacts health outcomes, yet there is a lack of recent prevalence data in Indonesia. Objective: This author initiated a study at Bekasi District Hospital, aiming to enhance awareness of malnutrition screening and assessment. Prompt nutritional interventions within the first 24 hours of hospitalization are crucial to prevent deterioration in nutritional status, reduce morbidity and mortality, shorten hospital stays, and lower healthcare costs.